Decoding the role of OsPRX83 in enhancing osmotic stress tolerance in rice through ABA-dependent pathways and ROS scavenging - Han Bao; Yuchao Cui; Xijun Zheng; Chengke Luo; Yan Li; Liang Chen (Plant Signaling & Behavior)
Plant Class III peroxidases have diverse roles in controlling root hair growth, anther development, and abiotic and biotic stress responses. However, their abiotic stress response mechanism in rice remains elusive. Here, we identified a peroxidase precursor gene, OsPRX83, and investigated its role in enhancing osmotic stress tolerance in rice. We used OsPRX83 overexpression and CRISPR-Cas9-generated mutant lines to elucidate OsPRX83‘s function and expression patterns under stress conditions. The expression of OsPRX83 was induced by H2O2, PEG, NaCl, and ABA treatments. Using qRT-PCR, RNA sequencing, and physiological assays, we demonstrated that overexpression of OsPRX83 enhanced the osmotic and oxidative stress tolerance as compared to the wild-type and mutant seedlings, as evident from the higher survival rates, enhanced peroxidase (POD) and ascorbate peroxidase (APX) activities, and increased ABA sensitivity compared with mutants and wild-type plants. Transcriptome analysis further supported the involvement of OsPRX83 in the ROS scavenging, by modulating the expression of OsDREB1B, OsDREB1E, OsDREB1F, OsDREB1G in response to osmotic treatment. In summary, our study suggests that OsPRX83 plays a pivotal role in enhancing stress tolerance in rice through ABA-dependent pathways and ROS scavenging. Therefore, this study elucidates the function of a novel abiotic stress response gene in rice, thereby may contribute to a new genetic engineering resource for engineering drought-resistant rice varieties.